ANALYSIS PERFORMANCE OF SEMARANG CITY FIRE DEPARTMENT) - Alifia Intan Saputri; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Semarang is included as one of big city in Indonesia with one of its vision is to advance trades and services. Hence, Semarang has developing and its advance establishment grown rapidly through the years. Rapid growth and development in Semarang inflict growing high risk of Fire to happen as well. Populous human population, high building growth, numerous running industry cause fire risk and whenever the fire happened, it requires specific handling process. Semarang Fire Department has its main duty which taking over government issues concerning fire and disaster prevention action in order to the principle of autonomy and assistance duty. This research has been done based on some problem occurred in program execution in the fire department. This research using qualitative descriptive research method with data collection technique by interview, observation, and documentation. The aim of this research is to analyze the performance of Semarang Fire Department and identify factors which support and resist organization’s vision accomplishment. Organization performance appraisal are according to effectivity, service quality, responsiveness, and accountability. Factors that may affect the working performance are seen from human resource, team work, and infrastructure. According to this research, performance of Semarang Fire Department is not on its best track yet, unreached target, worker tardiness in giving service to people, budget allocation within the incorrect target, alongside inadequate infrastructure to support the working performance so it can be concluded that the performance of Semarang Fire Department has not run well yet.